Impact of the implementation of tailored management strategies to reduce the occurrence of aflatoxin M1 in milk-supply chain in Italy. (July 2023) - Giacometti, Federica; Tomasello, Federico; Savini, Federica; Indio, Valentina; Bacak, Andelka; Canever, Alessandra; Bonilauri, Paolo; De Cesare, Alessandra; Serraino, Andrea
Abstract: In Europe the legal limit for aflatoxin M1 in raw milk, heat-treated milk and milk for the manufacture of milk-based products is set to 50 ng kg −1 . In Italy, an 'attention limit' of 40 ng kg −1 has been defined in 2013 for aflatoxin M1, while a more stringent attention limit of 30 ng kg −1 was set voluntarily by different regions in the following years. In this study we examined the data on aflatoxin M1 contamination in 67, 944 milk samples in the framework of the self-control plans of six milk industries in the periods 2004–2008 and 2013–2019. The proportion of positive samples showed a decreasing trend from 2004 to 2019 in relation to the compliance to the EU and both national limits. In addition, no seasonal aflatoxin M1 variation was evidenced after 2013. The data demonstrate how early and rapid detection of aflatoxin M1 applying a stringent self-control strategy resulting in the application of mitigation measures can significantly reduce the aflatoxin M1 concentration in milk. An update on the Estimated Daily Intake, the Hazard Index, and the fraction of hepatocarcinoma cases due to aflatoxin M1 exposure in different population groups, confirmed that infant and toddlers were more exposed than older consumers. Nevertheless, the application of an attention limit of 30 ng kg −1 further reduced the risk for young consumers. Taken all together our results demonstrate the efficacy of the tailored management strategies to limit the presence of aflatoxin M1 in milk implemented after the aflatoxin crisis in 2003 and 2013. Highlights: Milk AFM1 concentration has been evaluated in the framework of self-control plans. AFM1 contamination varied depending on the applied Attention Limit. Infants and toddlers were confirmed as more exposed to AFM1. AL 30 ng kg −1 led to a AFM1 contamination with a low risk for young population. No substantial seasonal AFM1 variation was evidenced.